Goal-setting in Islamic Banking: the Effects Of Personality And Perceptions Of the Goal-Setting Process on Job Satisfaction And Service Performance - Ratna Sundari Johar Sukadi (Prosiding Industrial Research Workshop and National Seminar, 2018)
This conceptual review shows the effect of setting conscious goals in terms of goal setting based on objectivegoals, transcendent goals and no goal setting that will result in the creation of personality and perception, whileat the same time job satisfaction will also have an impact on the creation of job satisfaction and improvedservice performance that results improvement of company performance. In other words, the development ofgoal-setting is based on religious grounds.